Dynamical quantum effects in multichannel nonlinear waveguides using phase space representations / Rafael Julius - Julius, Rafael (2019)
Squeezed light has a great deal of potential for varieties of quantum technology applications. In order to develop impactful devices reflective of wide application areas, technical difficulties of generating squeezing need to be eliminated or at least minimized. Therefore, in a search for a more flexible way of manipulating squeezing, the quantum effects exhibited by multichannel waveguides driven by coherent excitation are investigated. Four novel designs are considered: multichannel third order nonlinear waveguides, multichannel third order nonlinear waveguides with cavity setup and multichannel second order nonlinear waveguides, both with and without cavity setup. Compared to the multimode interaction in the standard two-channel configuration, the study focuses on developing a more convenient alternative to generate squeezed light via multichannel interaction considering the cross-action nonlinear coupling between the channel waveguides. In these implementations, solutions for the Hamiltonians of the proposed designs are obtained semi-analytically via normal- and symmetrical- ordered Phase Space Representation. Moreover, an effective computational program suitable for simulating dynamics of large quantum systems have been developed. The possibility for extending squeezing is investigated by studying the time development quadrature variances of the field’s averages. The results show that multichannel interaction exploiting third order nonlinear effect yields various forms of enhanced squeezing, as compared with the ordinary two-channel system. Maximal squeezing increases with the increase of channel waveguides involved in an interaction. In multichannel systems, there exist new possibilities for correlation between the modes in different channels, i.e. the second-, third- and fourth- order compound-mode. The states of maximal squeezing in the compound-mode depend upon the order of combination of field operators; the strongest squeezing always appears in the highest combination. Parallel squeezing (in all channels) is achievable via quantum state transfer, while the squeezing levels depend on the channels. As opposed to the asymmetrical initialization, symmetrical initial excitation provides a greater degree of squeezing and larger squeezing is possible with a larger input field. Fully quantum analysis of the intracavity dynamics displays a strong transition of photon property between the super-Poissonian and sub-Poissonian statistics. These transitions depend on the state of the cavity detuning. The cavity setup, in addition to the multichannel arrangement, allows different features of squeezing to be generated and enhanced squeezing is obtained for all the considered detuning values with an interesting effect such as leaf-revival-collapsed-like squeezing. In addition, the quantum effects are maximal near cavity resonance. Furthermore, in the case of second order nonlinear effect, the coupled modes can be sub-Poissonian over wide range of interaction length and a witness for bipartite entanglement between the modes in different channels is observed. Optimal entanglement is obtained by keeping the surrounding channels in isolation and the range for which maximal entanglement appear may be controlled by the number of channel waveguides. As such, the multichannel systems developed in this thesis provide complete mathematical models for emulating and extending the quantum effects, particularly squeezing.